LECTURERS’ CHALLENGES IN TEACHING EFL ONLINE USING ZOOM CLOUD MEETING - Ardy Herdiansyah; Yustika Nur Fajriah (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
Zoom Cloud Meeting is one software that can be used in online learning. Nevertheless, it is assumed that some obstacles were found while teaching online using this tool.  Departing from that point, this present study is an endeavour to investigate the lecturers' challenges in teaching EFL online using Zoom Cloud Meeting. A qualitative approach was used through a semi-structured interview. Three university lecturers were selected as the participants. The findings revealed that there were five challenges in teaching EFL online using Zoom Cloud Meeting. The first challenge was the lack of students' participation which made lecturers have to be more creative in teaching and make students happy to participate more. The second challenge was different students' characters, conditions, and readiness, The third challenge was lack of internet connection and lack of time. The last challenge was different uptake and understanding of students in receiving feedback. It can be concluded that it is necessary for lecturers to either follow some trainings regarding online teaching practice or getting involved in teachers’ discussion forum or organization to do sharing and finding more effective ways in teaching in the context of online teaching mode.